FRI0360 ANALYSIS OF BLOOD MONOCYTE TRANSCRIPTOMES AND BONE MARROW SAMPLES OF PATIENTS WITH AXIAL SPONDYLOARTHRITIS REVEALS THEIR CHANGES RELATED TO ACTIVATION AND MYELOPOIESIS. (June 2019) - Karow, Fabian; Grün, Joachim; Smiljanovic, Biljana; Poddubnyy, Denis; Erben, Ulrike; Kenngott, Elisabeth; Häupl, Thomas; Grützkau, Andreas; Syrbe, Uta
Abstract : Background: Axial spondyloarthritis (axSpA) is characterized by inflammation within the axial skeleton. Previously, we observed preactivation of circulating monocytes of axSpA patients suggesting systemic immune activation apart from local skeletal inflammation. Objectives: The aim of this study was to characterize systemic immune activation in axSpA by analyzing axSpA-specific monocyte transcriptomes and changes in myelopoiesis. Methods: We performed transcriptomic analyses using GeneChip HG-U133 Plus2.0 arrays of CD14+ monocytes isolated from peripheral blood of 25 HLA-B27+ axSpA patients and 10 healthy controls (HC). 10 patients were classified as non-radiographic axSpA (nr-axSpA) and 15 patients as ankylosing spondylitis (AS). Robust Multichip Averaging Algorithm normalization and high performance chip data analysis were used to select differentially expressed transcripts that define 1) axSpA-gene-expression profile and 2) profile that discriminates nr-axSpA from AS patients. Functional analysis of significant IDs was performed with Gene ontology (GO) and reference transcriptomes that portrayed myelopoiesis in bone marrow and monocytes activation with TNF, LPS, IFN and G-CSF. Myelopoiesis in bone marrow was studied by immunohistology according to MPO and CD15 expression in sections from facet joints of AS patients and controls (CO) without skeletal disease (n=6/group). Results: Comparison between axSpA and HC monocyte transcriptomes identified 957 differentially expressed transcripts that allowed separation of both groups by hierarchical clustering. GO analysis revealed associations of axSpA related transcripts with cell-cell adhesion, immune responses including Ras-signalling, Jak-STAT-signalling, innate immunity. Comparison of axSpA related transcripts with reference transcriptomes identified overlap with late myelopoiesis, pronounced mobilisation of monocytes from bone marrow into blood triggered by G-CSF and weak TNF/LPS activation. Nr-axSpA and AS monocytes differed in 562 transcripts. GO analysis of these transcripts suggested alterations in mitochondrial activity, peptide transport and DNA repair. According to reference transcriptomes, profiles of nr-axSpA monocytes differed from those in AS by gene patterns of late myelopoiesis and G-CSF triggered mobilisation from bone marrow. In histological analyses of bone marrow a significantly higher percentage of MPO+ cells indicative of left shifted granulopoiesis was found in AS vs. CO facet joints (p<0.01). Conclusion: AxSpA monocyte transcriptomes reflect weak immune activation by cytokine and/or LPS and premature release from bone marrow into blood. Bone marrow analysis shows a left shifted granulopoiesis in AS – both of which may contribute to pathological immune response within the skeleton in axSpA. Reference: [1] Conrad K, Wu P, Sieper J, Syrbe U. In vivo pre-activation of monocytes in patients with axial spondyloarthritis. Arthritis Res Ther. 2015Jul16;17:179. Doi: 10.1186/s13075-015-0694-2. PubMed PMID: 26178906 Disclosure of Interests: Fabian Karow: None declared, Joachim Grün: None declared, Biljana Smiljanovic: None declared, Denis Poddubnyy Grant/research support from: AbbVie, Merck Sharp & Dohme, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB Pharma, Ulrike Erben: None declared, Elisabeth Kenngott: None declared, Thomas Häupl: None declared, Andreas Grützkau: None declared, Uta Syrbe: None declared